Perceptual distance in coaching beginning teachers: a dyadic study of coaches’ basic psychological need support and coachees’ need satisfaction - Liu, Hugh Jiliang; De Jonge, Kiki M. M.; Den Hartigh, Ruud J. R.; Van Yperen, Nico W. (Frontiers in Education, 2025)
IntroductionSelf-Determination Theory (SDT) has been widely applied in coaching to support coachees’ needs for autonomy, competence, and relatedness, which are collectively known as Basic Psychological Needs (BPNs). Although these BPNs are typically viewed as interpersonal constructs, there is a notable lack of dyadic studies that examine these interpersonal dynamics in the context of coaching beginning teachers. Addressing this gap is crucial, as discrepancies often exist between the perceptions of coaches and coachees concerning BPN support. Therefore, this study aimed to investigate this perceptual distance and its association with coachees’ BPN satisfaction.MethodsA sample of seventy-two dyads, consisting of coaches and their coachees (i.e. beginning teachers), completed self-report surveys immediately after completing their coaching program. We used polynomial regression and response surface analysis to examine the relationship between the perceptual distance and coachees’ BPN satisfaction.ResultsThe results revealed three groups of dyads: (1) dyads where coaches overreported their BPN support (i.e. reported their own behaviour more positively than their coachee did, ~ 31%), (2) dyads where coaches underreported their BPN support (i.e. reported their own behaviour less positively than their coachee did, ~ 27%), and (3) dyads where both parties agreed on the level of BPN support (~ 42%). Moreover, we found that coachees experienced higher BPN satisfaction when both parties agreed rather than disagreed. When perceptions aligned, BPN satisfaction was highest under high BPN support. When perceptions diverged, coachees’ BPN satisfaction was higher when coaches underreported rather than overreported.DiscussionThese findings underscore the importance of aligning coaches’ and coachees’ perceptions through self-reflection and communication, while also emphasising the need for future dyadic-level research in education and beyond.